Assessment of functional ability by anthropometric and physiological parameters during six-minute walk test in healthy children - Khalid, Maria; Arshad, Hafsah; Kiyani, Sania Khawar; Batool, Fouzia; Zainab Saad; Aleena Hameed (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the functional ability and vitals of young children using six-minute walk test. Method: The analytical cross-sectional study was conducted from October 2019 to January 2020 at public and private schools of Rawalpindi and Islamabad after approval from the ethics review committee of Riphah College of Rehabilitation Sciences, Westridge Campus Rawalpindi, Pakistan, and comprised healthy children aged 7-12 years who were subjected to the six-minute walk test according to standardised guidelines. Data was collected using a semi-structured questionnaire. Anthropometric measurements, distance walked in six minutes, heart rate, respiratory rate, oxygen saturation, and rate of perceived exertion were the outcome variables. Data was analysed using SPSS 26. Results: Of the 376 subjects, 225(59.8%) were boys and 151(40.2%) were girls. The mean age of the sample was 9.25±1.64 years. Mean distance covered by the children was 482.63±119.76 metres. Public school students performed better than those studying in private schools (p=0.001). The difference in gender terms was non-significant (p=0.926). Significant difference was observed in mean heart rate and respiratory rate post-walk (p<0.05). There was a weak positive correlation of the test with age and height (p<0.001), but not with weight, gender and body mass index (p>0.05). Conclusion: The level of functional ability of the young students improved with age and was better among those studying at public schools. Besides, anthropometric and physiological parameters influenced the text performance. Key Words: Children, Six-minute walk test, Heart rate, Perceived exertion.